Simultaneously Achieving Ultrahigh Sensitivity and Wide Detection Range for Stretchable Strain Sensors with an Interface‐Locking Strategy. Issue 5 (2nd April 2020) - Lin, Waner; He, Chubin; Huang, Huayi; Zhao, Wenyu; Qiu, Yanbing; Guan, Xiao; Zhang, Qi; Wang, Ziya; Peng, Zhengchun
Abstract: The development of stretchable strain sensors is crucial for the implementation of electronic skins and wearable electronics. Resistive‐type strain sensors are typically composed of an electrically conductive sensing layer coupled to a stretchable substrate. When a sensor is stretched, microstructural changes in the sensing layer lead to a strain‐dependent change in resistance. However, strain sensors with high sensitivity and specificity often suffer from a limited detection range along with reliability issues. Here, a novel strain sensor composed of Ag particles and long‐range entangled carbon nanotubes (CNTs) with a special composite design is proposed, in which a strain‐induced self‐locking effect is introduced at the interface between the CNT film and a percolating network consisting of Ag particle filler. As a result, the sensors achieve significantly enhanced performance such as large stretchability (≥120%), high gauge factor (3990.8), fast response time (<33 ms), and high mechanical durability. A range of wearable applications including radial artery, facial expression, and joint motion monitoring are demonstrated, which range from minute deformation to excessive stretching of the sensor. Abstract : A highly stretchable and sensitive strain sensor based on interface‐locked Ag particles is realized by a carbon nanotubes (CNT) network. The sensor is prepared with a facile, cost‐effective, and scalable approach. It can accurately measure strains from a delicate deformation to an intensive stretch, as demonstrated by pulse detection, facial expression, and hand gesture recognition, and joint movement monitoring.